Sistem Pakar Diagnosa Penyakit Pada Burung Murai Serta Cara Mengatasinya - Pudji Widodo - AMIK BSI Yogyakarta; Anjar Andi Priyanto - AMIK BSI Purwokerto (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2018)
ABSTRACT - Expert system for diagnosing the humming bird and how to overcome this is an expert system that is designed as a tool for users to diagnose diseases of the magpies of analysis by a humming bird breeders. Knowledge of this expert system has many sources including research and observations that have been in practice by a humming bird breeders and issued either through web resources and other resources such as manuals, and others. The basis of this expert system is a database that is compiled into a table and then enforced the rules so that users can draw conclusions from what has been diagnosed by this expert system. This expert system will show the questions that will then be selected by the user to find the answer to this expert system. Additionally, this expert system will also provide information about the disease in a humming bird and solutions to overcome them.Keywords: Expert System, Bird Magpie, Database. ABSTRAK - Sistem pakar untuk mendiagnosa pada burung murai serta cara mengatasinya ini merupakan sistem pakar yang di rancang sebagai alat bantu pengguna untuk mendiagnosa penyakit pada burung murai dari analisa menurut peternak burung murai. Pengetahuan dari sistem pakar ini mempunyai banyak sumber diantaranya penelitian dan pengamatan yang sudah di praktekan oleh peternak burung murai dan dikeluarkan baik melalui sumber web dan sumber lain seperti buku manual, dan lain-lain. Basis dari sistem pakar ini adalah database yang disusun ke dalam table lalu ditegakan aturan agar pengguna dapat mengambil kesimpulan dari apa yang sudah di diagnosa oleh sistem pakar ini. Sistem pakar ini akan menampilkan pertanyaan yang kemudian akan dipilih oleh user sampai menemukan jawaban dari sistem pakar ini. Selain itu sistem pakar ini juga akan memberikan informasi tentang penyakit pada burung murai dan solusi untuk mengatasinya.Kata kunci: Sistem Pakar, Burung Murai, Database.